Multiculturalism and Islamic Education in Western Contexts: Navigating Identiity, Faith, and Citizenship - Ubaidillah Ubaidillah; Irmak Sude Gürel (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
Islamic education in Western countries serves as a strategic space for shaping the dual identities of Muslim students as faithful individuals and as citizens in democratic and multicultural societies. This study explores how Islamic institutions and educators in the West integrate civic values, multiculturalism, and Islamic teachings into educational practices. Using a systematic literature review (SLR) method with an exploratory qualitative approach, the study analyzes 10 scholarly articles, sourced from Scopus, Sinta, and Google Scholar. The findings reveal four key themes: (1) Islamic education functions as a space for negotiating dual identities among Muslim students; (2) there is active integration of civic values such as tolerance, social responsibility, and justice into Islamic curricula; (3) Muslim educators play a strategic role as cultural mediators and transformative agents in building inclusive identities; and (4) structural challenges persist, including institutional discrimination, restrictive secular policies, and limited policy support. This study affirms that Islamic education in the West is not merely a vehicle for religious preservation, but also a strategic platform for cultivating participatory, democratic, and pluralistic citizenship.